Afghanistan's Free Fall – Return of the Taliban and Flight as a Last Resort - Clara Albrecht; Britta Rude; Tanja Stitteneder (CESifo Forum, 2021)
Afghanistan is one of the poorest countries in the world. In 2020, almost half of the population lived in poverty, and 19.1 million people were hungry. One in three children under the age of five is underdeveloped, and six in ten women experience physical and/or sexual violence in their lifetime. The country ranks last on the Global Peace Index in 2021. Political, economic, social, and environmental factors are driving flight and migration in and out of Afghanistan. The withdrawal of international troops, the return of the Taliban, and the decline in development aid are exacerbating the situation. As of early September 2021, nine out of ten Afghans are suffering from food shortages, and the stagnation of the financial sector poses a problem for aid organizations. Many Afghans are being forced to leave their homes, with internal migration accounting for the majority of migration in Afghanistan. Of those who dare to flee abroad, most move to neighboring Pakistan and Iran. The two countries currently host about 80 percent of Afghan migrants; in comparison, only a few are heading to Western countries.
Keywords: 330